A Unified framework for spacecraft operations - Verrier, David (Cranfield University, 2001)
This work analyses the current state of the art in the Spacecraft Operations domain. It reviews the structure and practices within the European space industry and shows how the industry is generally shaped by national or international non-governmental organisations. Although it draws most material from the author's experience in Europe whilst working on commercial space projects and international scientific projects, it compares and contrasts this with the US manned space programme and the Russian space programme. The space industry in Europe has inefficient working practices and a poor market structure which lacks incentives. The civil service-based organisations that administer the majority of national and European space activity have a poor internal organisation, are often slow to react, exhibit little delegation and reduce individual initiative. Recommendations are made about industrial policy, and how organisations should approach risk management and how teams should be formed and should interact. The spacecraft and instruments are normally built by specialised teams and organisations. This results in a conceptual gap between those who acquire knowledge whilst building and testing the systems and those who will operate the system. It is necessary to explicitly transfer the knowledge to the operations team, and there are weak mechanisms for doing so. At the same time, the operations team also has to prepare the ground segment to control a spacecraft and exploit a payload that, from their point of view, may be poorly defined. It is proposed that the traditional paper-based products (user manual and flight procedures) could be usefully supplemented or replaced by a knowledge base. An ontology to define a vocabulary is developed and it is shown to facilitate knowledge capture and exploration. The availability of such a facility would then also assist future missions (or even missions running in parallel) to understand the problems that their colleagues have, and adapt or incorporate the solution if it was applicable. There is a significant trend for spacecraft to become more complex and to have many computers and a great deal of software on-board. This make the system difficult to operate, and can also lead to unexpected results, since the state space of a software-driven system is so large. For terrestrial systems, formal methods have been developed to try to counteract the trend: by proving certain behaviour in the specification, the number of paths that need to be tested can be significantly pruned. It is proposed here that formal methods could be adopted to test and communicate knowledge, as well as to improve the design. The trend to have increasingly intelligent sub-systems has been occurred in parallel to the trend to have increasingly sophisticated data communication. This is applicable equally to command and monitoring. The information content of parameters is analysed, and the content of flags and simple packets is calculated.